Draft genome sequence of the first human isolate of the ruminant pathogen Mycoplasma capricolum subsp. capricolum - Seersholm, F.V.; Fischer, A.; Heller, M.; Jores, Joerg; Sachse, K.; Mourier, T.; Hansen, A.J. (American Society for Microbiology, 2015)
Mycoplasma capricolum subsp. capricolum is a well-known pathogen of small ruminants. A recent human case of septicemia involving this agent raised the question of its potential pathogenicity to humans. We present the first draft genome sequence of a human Mycoplasma capricolum subsp. capricolum isolate.